2019
DOI: 10.1108/jes-06-2018-0222
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the nonlinear “knots” of UK’s housing prices

Abstract: Purpose Housing prices in the UK offer an inspiring, yet a complex and under-explored research area. The purpose of this paper is to investigate the critical factors that affect UK’s housing prices. Design/methodology/approach The authors utilize the recently developed nonlinear ARDL approach of Shin et al. (2014) over the period 1969–2016. Findings The authors find that both the long-run and short-run impact of the price-to-rent (PTR) ratio and credit-to-GDP ratio on house prices (HP) is asymmetric whilst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…It should be stressed that even though the specific methodology takes care of a mixed order of integration, i.e., I(0) and I(1), we have also checked for unit roots to ensure that none of the series is I(2) (Alexiou and Vogiazas 2019). The unit root tests in Appendix A (Table A1) indicated that all other series are integrated of order 1, i.e., I(1).…”
Section: Methodsmentioning
confidence: 99%
“…It should be stressed that even though the specific methodology takes care of a mixed order of integration, i.e., I(0) and I(1), we have also checked for unit roots to ensure that none of the series is I(2) (Alexiou and Vogiazas 2019). The unit root tests in Appendix A (Table A1) indicated that all other series are integrated of order 1, i.e., I(1).…”
Section: Methodsmentioning
confidence: 99%
“…1. Examples of other studies that included income and mortgage rates are: Chen and Patel (ss), Apergis (2003), Apergis and Rezitis (2003), Abelson et al (2005), Gallin (2006), Chen et al (2007), McQuinn and O’Reilly (2008), Rapach and Strauss (2009), Kim and Bhattacharya (2009), Mikhed and Zemcik ( 2009 ), Adams and Fuss (2010), Zhou (2010). Holly et al (2010), Madsen (2012), Apergis et al (2015), Antonakakis et al (2015), Bahmani-Oskooee and Ghodsi (2017), Bahmani-Oskooee and Ghodsi (2018), Baghestani and Viriyavipart (2019), Alexiou and Vogiazas (2019). Alola (2020), De Albuquerquemello and Bessarria (2021) and Cuesta and Kukk (2021).…”
Section: Notesmentioning
confidence: 99%